Pengelolaan Prakerin Program Keahlian Teknik Elektronika di SMK Muhammadiyah 1 Sukoharjo - Sunardi, Sunardi, Prof.Dr.Bambang Sumardjoko, Dr. Wafrotur Rohmah, M.M (2016)
Sunardi, Q 100140066, Masters in Education Administration, Graduate Program, University of Muhammadiyah Surakarta.2016. The purpose of this study is (1).To describe the characteristics of the planning prakerin program membership electronics engineering at SMK Muhammadiyah 1 Sukoharjo, (2).To describe the characteristics of the implementation Prakerin program membership electronics engineering at SMK Muhammadiyah 1 Sukoharjo, (3).To describe the characteristics of the planning Prakerin program engineering expertise electronics in SMK Muhammadiyah 1 Sukoharjo. The research is a qualitative research with descriptive design. Sources in the research is the principal, vice-principal, the chairman of the working group prakerin, head of program membership, earning of teachers and industry leaders. Methods of data collection are observation, interview, and documentation. Analysis of data using an interactive model. The results of the study are (1).Planning prakerin include: mapping industry, the program prakerin, time prakerin, debriefing prakerin, and the establishment of a tutor, (2).Implementation of prakerin include organizing student submissions prakerin to industry, monitoring students prakerin, and withdrawal of students prakerin to School. (3).Ratings prakerin there are two phases: assessment by tutors industry and counselors School with a parameter value of the industry (IN) is weighted 60%, the value of the journal prakerin (JP) is weighted 10%, the value of the oral exam (UL) is weighted 20 %, and the value of the report (LP) is weighted 10%. So that the total value of the results prakerin students are: 0.6 (IN) + 0.1 (JP) + 0.2 (LP) +0.1 (LP). Keywords: management, prakerin, electronics engineering program